2019
DOI: 10.2478/cait-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Various Techniques Involved in Gender Prediction System: A Comprehensive Review

Abstract: Predicting gender on the foundation of handwriting investigation is a very invoking research area. Handwriting analysis also has numerous applications. It is useful for forensic experts to investigate classes of writers. This prediction is executed fundamentally by two steps: feature extraction and classification. As a whole, prediction solely depends upon the feature extraction. Distinct and most varied features make the classification accurate. This paper describes the problem comprehensively along with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Dargan and Kumar [26] identified the writer and gender prediction in Gurumukhi script using hybridization of classifiers and estimated accuracy of 87.76% and 90.57%, respectively. Maken and Gupta [27] demonstrated a technique for offline handwriting-based gender classification systems using area, perimeter, and slanteness features and logarithmic regression, KNN, and SVM as classification methods to achieve high performance of the system.…”
Section: Related Workmentioning
confidence: 99%
“…Dargan and Kumar [26] identified the writer and gender prediction in Gurumukhi script using hybridization of classifiers and estimated accuracy of 87.76% and 90.57%, respectively. Maken and Gupta [27] demonstrated a technique for offline handwriting-based gender classification systems using area, perimeter, and slanteness features and logarithmic regression, KNN, and SVM as classification methods to achieve high performance of the system.…”
Section: Related Workmentioning
confidence: 99%
“…Feature extraction and classifier training are the main foundations of these techniques. The literature research demonstrated that machine learning and deep learning methods had been successfully employed for classifying a writer's demographics [16]- [18], [22]. Despite their effectiveness, a fundamental problem in these deep learning-based systems is the availability of massive training data sets and powerful computing resources.…”
Section: Issn: 2302-9285 mentioning
confidence: 99%
“…A new method based on hinge feature and cloud of line distribution (COLD) is proposed by Gattal et al [17] to be used to identify the gender from handwriting. A number of studies mentioned in [18]- [20] validated the relationship between gender and handwriting. In these studies, a comparative analysis of the mentioned methods of feature extraction and classification, as well as the accessible datasets, is also presented.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of traffic, humans, and any object can be done by such imaging. Many other industrial applications like speed determination, face detection [17], object recognition [54], object identification, document handling, character recognition [8], handwriting recognition [68], texture analysis [100], etc. are based on imaging in the visible spectrum.…”
Section: Imaging Techniques For Image Processingmentioning
confidence: 99%